Pendidikan Akhlak Mewujudkan Masyarakat Madani - Ghani, Ainul (Universitas Islam Negeri Raden Intan Lampung, 2015)
Islamic education is important role in development and society as a key for continuity in the society. Islamic education in various problem both internally and ekstern required to be able to answer the challenges.There are problems of the value of, as the concept, the credibility gap and idealism.Efforts acceptable solution to this problem is a recipe for the center of islamic education, revitalize education of education and establish a global (International Islamic University) all that is to foster a conducive situation for development of islamic education and good